Reflexology On Blood Sugar Levels In Patients With Diabetes Mellitus: Literature Review - Wiratama, Rahardyan Dika; Muhith, Abdul; Zahro, Chilyatiz (Journal of Applied Nursing and Health, 2023)
Background: Diabetes mellitus is a disease that often causes chronic complications if not handled properly and is characterized by an increase in blood sugar levels. This literature review aims to determine the effect of reflexology on blood sugar levels in patients with diabetes mellitus. Methods: The method used in this article is a literature review using a journal database from Science Direct and Google Scholar from 2020 to 2023 with the keywords "Reflexology" or "Reflexology," "Blood glucose" or "Blood sugar levels," and "Diabetes Mellitus" Results: obtained results of 1,070 articles. Articles were selected according to the criteria, and ten articles were ready to be reviewed.  Reflexology affects lowering blood sugar levels in people with diabetes mellitus by doing it regularly for 20-30 minutes 12 times. Conclusion: Doing a physical activity, one of which is applying Reflexology 12 times in 3 sessions for four weeks, can control blood sugar levels